IIGEO online magazine: History, database, statistical and forecasting - Lovera, Daniel (2013)
The Institute of Investigation magazine IIGEO, from the beginning, is dealing with relevant subjects in mining, the environment and sustainable development. Its incorporation as virtual magazine into the system of libraries (SISBIB) allowed to spread it over a large number of visitors. Subsequently, the magazine was entered into the Indexed Bases like LATINDEC and SCIELO PERU, achieving a major virtual presence in internet. In recent years, we worked for sharing OJS Base (Open Journal System). This initiative is promoted by the UNMSM Vice Rector of investigation in order to incorporate the university institutes of investigationpublications. IIGEO is considered among the best UNMSM virtual magazines like Annals of Medicine (Anales de Medicina), Biological Peruvian Magazine (Revista Peruana de Biología) and Peruvian Investigations of Veterinary Magazine (Revista de Investigaciones Peruanas de Veterinaria).